State as an Heir: Balancing Public and Private Interests in Georgia and Europe. Part II: Dilemma of the State as Legal Successor - Irakli Leonidze (Review of European and Comparative Law, 2025)
As previously stated in Part I, Article 1343 of the Civil Code of Georgia establishes the state as a “sixth-degree” heir, signifying that the state possesses a legitimate public interest in acquiring heirless property. Considering the state as a heir in the same capacity as individuals would conflict with the private interests of those individuals, particularly when they might have a legitimate claim to the heirless property. It is vital to circumscribe the state’s involvement to the minimum necessary in order to fulfil its public interest. The Part II of the article is dedicated to an examination of the dilemma faced by the state in its capacity as legal successor, posing the question of whether it should assume the role of “sixth degree” heir or defender of the public order.